Public diplomacy as an instrument of US foreign and security policy - Gorenc, Nina (Teorija in praksa, 2019)
The article analyses the role played by public diplomacy (PD) in the foreign and security policy of the United States of America. Relying on content analysis of publicly available official budget tables, national security documents and reports, we researched the relationship between PD and its funding, the challenges PD faces in the new digital environment, and its importance in the foreign and security policy setting. Content analysis helped detect the presence, meaning and relationships of words and concepts related to PD in the mentioned documents. We show a substantial difference exists between the declared importance of PD on one side, and its financing and ascribed role in foreign and security policies on the other.
Keywords: Analiza vsebine; Content analysis (Communication); digitalno okolje; Diplomacija; Diplomacy; Foreign policy; javna diplomacija; mehka moč; Nacionalna varnost; National security; Zunanja politika